Understanding conceptual text sand master in gconcepts - Tsukerman G.A.,; Kleshch.N.A., (Психологическая наука и образование, 2017)
We address the issue of the relationship between conceptual thinking and understanding of conceptual texts only from the following angle: whether or not can working towards a profound understanding of texts that describe concepts promote the use of these concepts in unusual tasks. Employing the methods of classical statistics and factor analysis, we compare the metasubject outcomes of primary education in two samples of children that differ only in one teaching factor: the experimental classes were consistently working on creating and using conceptual texts. The principle of this teaching work was to establish a situation of bilingualism when introducing new concepts: to write down new characteristics of the studied subject in the language of graphical schemes and at the same time in verbal form and to translate sentences about this subject from one language into another. As it was revealed, this specially organized work with conceptual texts results in the following: (1) an increase in the level of mastery of learnt concepts if these concepts are presented in verbal form; (2) a better understanding of information texts with unfamiliar conceptual content, that is, one of the key elements in self-learning emerges.